STRATEGIC MANAGEMENT OF SEXUAL VIOLENCE VICTIMS SERVICES A CASE STUDY OF DP2PA SAMARINDA CITY - Serly Fitriana; Muhammad Arif Nurrahman (SOSIOEDUKASI, 2026)
This study analyzes the service strategies of the Women's Empowerment and Child Protection Agency (DP2PA) of Samarinda City in handling victims of sexual violence from a strategic management perspective, which includes planning, implementation, and evaluation. A structured service strategy is crucial to ensure that the handling of sexual violence victims is carried out effectively, coordinated, and responsive to the needs of the victims, especially amidst the increasing cases of violence against women . The findings indicate that the service strategy planning has been systematically formulated in the Action Plan and Work Plan (RENJA) documents, which include objectives, programs, performance indicators, and budget allocations. The implementation of the strategy is carried out thru cross-sector synergy, complaint mechanisms, legal and psychological assistance, and an integrated referral system involving law enforcement agencies, health institutions, and legal aid organizations. Additionally, strategy evaluation is conducted thru control mechanisms and performance assessments to ensure the achievement of service targets. However, this study also reveals several challenges, including budget constraints, inadequate number and capacity of human resources, suboptimal cross-sector coordination, and low public awareness in reporting sexual violence cases. These constraints limit the effectiveness of service strategies in producing more substantial protection impacts. This study concludes that strengthening institutional capacity, increasing budget support, optimizing coordination, and enhancing community participation are essential to realizing a more effective and sustainable victim protection service system for sexual violence.